2019
DOI: 10.1097/jxx.0000000000000328
|View full text |Cite
|
Sign up to set email alerts
|

An innovative technique to promote understanding of anatomy for nurse practitioner students

Abstract: Nurse practitioner (NP) students are required to have a clear understanding of the complexities of the human body. Students enter graduate studies with varying experiences and backgrounds in anatomy and physiology. Evidence suggests that human anatomy laboratories increase learning outcomes when compared with comparative anatomy modalities. The purpose of this evaluation was to determine if teaching with a computed tomography (CT)-based three-dimensional (3D) anatomy table and cadaveric specimens improves Doct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Three-dimensional visualization technologies now offer new approaches to teaching and learning anatomy. 2,5,6 Traditional approaches such as cadaver dissections are complemented with technologies like two-dimensional (2D) and three-dimensional (3D) digital imaging to investigate and learn the anatomy of the human body. 7,8 In the literature, the term 3D technology has various meanings.…”
mentioning
confidence: 99%
“…Three-dimensional visualization technologies now offer new approaches to teaching and learning anatomy. 2,5,6 Traditional approaches such as cadaver dissections are complemented with technologies like two-dimensional (2D) and three-dimensional (3D) digital imaging to investigate and learn the anatomy of the human body. 7,8 In the literature, the term 3D technology has various meanings.…”
mentioning
confidence: 99%
“…Visual aids are widely used in both in-person and online nursing education. Various methods of imparting knowledge of anatomy to nursing students have been tested worldwide: video-based lectures in Egypt (El-Sayed & El-Sayed, 2013), kinesthetic learning activities in the United States (Wagner, 2014), hands-on games and puzzles in Australia (Salvage-Jones et al, 2016), interdisciplinary theoretical-practical activities in Brazil (Ratero et al, 2020), and virtual anatomy tables (Whited et al, 2019;Bianchi et al, 2020;Narnaware & Neumeier, 2021).…”
Section: Anatomical Science Pedagogymentioning
confidence: 99%
“…Most pedagogical strategies lead to positive learning outcomes for undergraduate students and increase confidence in knowledge of anatomy among nurse practitioners and nursing doctorate students (Whited et al, 2019). Doctor of nursing practice and nurse practitioner students have reported that three-dimensional anatomy tables alongside prosected human cadavers can strengthen their ability to identify pathologies in virtual case studies (Whited et al, 2019).…”
Section: Anatomical Science Pedagogymentioning
confidence: 99%
See 2 more Smart Citations